Polio immunization in Pakistan: ethical issues and challenges - Basharat, Sarah (Public Health Rev, 2017)
BACKGROUND: Immunization should be considered a basic human right to health and well-being. It is everybody’s business, and it is everybody’s responsibility: the individual, the community, the health system and the state. This paper attempts to review some of the literature that highlights the ethical and religious concerns surrounding polio vaccination and what approaches may be used to counter the problems faced in Pakistan. METHODS: This paper is developed through a literature review on public health and polio in Pakistan, consulting local, regional and globally published peer reviewed articles focussing on religion, culture, ethics and public health. DISCUSSION: Human behaviour, including the utilization and acceptability of healthcare services, is greatly influenced by religious beliefs and dogmas. Immunization, specifically for the purpose of polio eradication, has been a topic under focus and in the news in Pakistan. The government is doing its best through a variety of interventions to increase access, inform the public and increase vaccination rates. Nevertheless, the country still faces a huge challenge from certain stern pockets of uncompromising populations who resist and refuse vaccination. Beliefs, practices and cultural norms overshadow public health priorities and ethics. Understanding of the context, therefore, is critical to determine the social hindrances in polio eradication and strategize thereon. CONCLUSION: Having programmatic, system-wide, socio-cultural and of course ethical dimensions, the policy makers and the programme managers in Pakistan must attempt to address the multitude of challenges to polio vaccination, whereby the plan of action developed within the ethical norms could potentially lead to an ultimate success.